Integration of PCK, Digital Literacy, and Learning Design Skills: Factors Influencing Impactful Elementary Teaching - Sundahry; Syahrial; Yantoro; Destrinelli (International Journal of Elementary Education, 2025)
The main problem in teacher education lies in the suboptimal integration of Pedagogical Content Knowledge (PCK), digital literacy, and instructional design skills in authentic teaching practice. The integration of these competencies remains emergent among prospective teachers who are transitioning to professional practice. This study aims to explore the integration of these competencies in achieving impactful learning. This research employed a qualitative approach with a phenomenological design. The participants consisted of 15 final semester students from a teacher education program. Data were collected through semi structured Forum Group Interviews (FGI) and analyzed using thematic analysis based on Creswell’s six step model.The findings indicate that prospective teachers possess foundational understanding of each competency; however, their integration remains gradual. Five major themes were identified impactful instructional design, integration of PCK and technology, digital literacy practices, systematic instructional design processes, and facilitating and hindering factors. Field experience emerged as the most transformative factor in shifting perspectives toward a pedagogy first orientation.The study concludes that competency integration depends on authentic experiences, consistent pedagogical modeling, and structured reflection. The implication is that teacher education programs should strengthen field practice, mentor collaboration, and design based learning challenges to accelerate the integration of competencies.